Probabilistic seismic hazard assessment of Lisbon (Portugal) - Gögen, Büşra (2024)
The 1755 Lisbon earthquake holds significant historical importance in Portuguese history. The subsequent tsunami resulted in extensive destruction and damage, affecting not only Lisbon but also other regions of Portugal, Spain, and North Africa. This significant and hazardous event led to an increase in awareness about earthquake and tsunami risks, not only within Portugal but throughout Europe. This heightened awareness facilitated advancements in scientific developments, including design codes, standards, and earthquake engineering. However, recent studies focusing on hazard assessment for Lisbon are limited. For this reason, this paper aims to present a comprehensive probabilistic seismic hazard analysis (PSHA) for the Lisbon metropolitan area. The first stage of PSHA involves defining applicable and active seismic source models (area and line sources) within the study area. Subsequently, historical and instrumental earthquake records are collected to build a homogenized earthquake catalog, utilizing both global and local earthquake databases. Following this, the completeness level of the earthquake catalog is tested. By incorporating suitable ground motion models to the region and local soil characteristics, seismic hazard maps for various return periods and hazard curves in terms of peak ground acceleration (PGA) are developed. The findings based on the area source model agree with existing literature, indicating PGA values ranging from 0.3 g to 0.9 g, 0.2 g to 0.7 g, 0.2 g to 0.5 g, and 0.1 g to 0.3 g for return periods of 2475, 975, 475, and 50 years, respectively.